Association of Emotion Regulation Trajectories in Childhood With Anorexia Nervosa and Atypical Anorexia Nervosa in Early Adolescence - Henderson, Mariella (JAMA Psychiatry, 2021)
IMPORTANCE: People with anorexia nervosa often experience difficulties regulating their emotions. There is no longitudinal evidence as to whether these differences are already present in childhood or when they begin to emerge. OBJECTIVE: To investigate the association between emotion regulation trajectories from 3 to 7 years of age and symptoms of anorexia nervosa and atypical anorexia nervosa in adolescence. DESIGN, SETTING, AND PARTICIPANTS: This cohort study included all children with complete exposure data in the Millennium Cohort Study, a UK general population birth cohort. Data were acquired from June 2001 to March 2016 and analyzed from June to November 2020. EXPOSURES: Mothers reported on their children’s emotion regulation skills at 3, 5, and 7 years of age using the Children’s Social Behavior Questionnaire. Multilevel models were used to derive early childhood emotion regulation scores (ie, predicted intercept) and within-child changes in emotion regulation scores from 3 to 7 years of age (ie, predicted slope). MAIN OUTCOME AND MEASURES: Symptoms consistent with a DSM-5 diagnosis of anorexia nervosa or atypical anorexia nervosa at 14 years of age, defined using a range of questions relative to body image, weight perception, and dieting behaviors (hereinafter referred to as broad anorexia nervosa). Univariable and multivariable logistic regression models tested the association between exposures and outcome. Regression models were adjusted for child and family sociodemographic and socioeconomic characteristics and mental health difficulties, prenatal and perinatal factors, child’s cognitive development, and maternal attachment. RESULTS: A total of 15 896 participants (85.7% of total sample; 51.0% boys; 84.5% White individuals) had complete data on the exposure and were included in the main analyses. Among those with complete exposure and outcome data (9912 of the analytical sample [62.4%]), 97 participants (1.0%; 86 [88.7%] girls and 85 [87.6%] White individuals) had symptoms consistent with a diagnosis of broad anorexia nervosa at 14 years of age. No evidence suggested that children with lower emotion regulation ability at 3 years of age had greater odds of later reporting symptoms of broad anorexia nervosa (odds ratio [OR], 1.21; 95% CI, 0.91-1.63). However, children whose emotion regulation skills did not improve over childhood and who had greater problems regulating emotions at 7 years of age had higher odds of having broad anorexia nervosa at 14 years of age (OR, 1.45; 95% CI, 1.16-1.83). CONCLUSIONS AND RELEVANCE: These findings suggest that difficulties in developing age-appropriate emotion regulation skills in childhood are associated with experiencing broad anorexia nervosa in adolescence. Interventions to support the development of emotion regulation skills across childhood may help reduce the incidence of anorexia nervosa.